Comparison between selective harmonic elimination and nearest level control for transistor clamped H-bridge inverter - Wail Ali Ali Saleh; Nurul Ain Mohd Said; Wahidah Abd Halim; Auzani Jidin (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Total harmonic distortion (THD) is a key index used to measure the quality of output waveforms in multilevel inverters. In this paper the THD is investigated and compared between two modulation methods; selective harmonic elimination and nearest level control, for 13-level transistor clamped H-bridge (TCHB) inverter. The selected TCHB topology employs a reduced number of DC sources and switches compared with other conventional multilevel inverters, which helps to reduce the size and cost of the inverter. The performance of both modulation methods has been validated through simulations using MATLAB/Simulink. The results show that for selective harmonic elimination, the 13-level output exists for a narrow range of modulation index, M (0.687≤M≤0.694),while for nearest level control method, the 13-level output exists for a wider range of M (M≥0.917), which means the 13-level output exists for different ranges of  for both methods. The THD obtained from both methods fulfills the IEEE Std 519-2014 standard of harmonics. Nearest level control method is conceptually simple and produces better THD results compared with selective harmonic elimination method.distortion (THD) is a key index used to measure the quality of output waveforms in multilevel inverters. In this paper the THD is investigated and compared between two modulation methods; selective harmonic elimination and nearest level control, for 13-level transistor clamped H-bridge (TCHB) inverter. The selected TCHB topology employs a reduced number of DC sources and switches compared with other conventional multilevel inverters, which helps to reduce the size and cost of the inverter. The performance of both modulation methods has been validated through simulations using MATLAB/Simulink. The results show that for selective harmonic elimination, the 13-level output exists for a narrow range of modulation index,  (), while for nearest level control method, the 13-level output exists for a wider range of  (), which means the 13-level output exists for different ranges of  for both methods. The THD obtained from both methods fulfills the IEEE Std 519-2014 standard of harmonics. Nearest level control method is conceptually simple and produces better THD results compared with selective harmonic elimination method